SOCIO‑ECONOMIC DRIVERS AND INSTITUTIONAL CHALLENGES OF TOBACCO CONTRACT FARMING PARTICIPATION IN SVOSVE COMMUNAL AREA, ZIMBABWE - Nyakuchena, Nyasha; Musara, Joseph P.; Mwakiwa, Emmanuel (Applied Studies in Agribusiness and Commerce, 2026)
Tobacco remains Zimbabwe's Leading agricultural export crop, increasingly produced under contract farming arrangements. While contract farming offers inputs, technical assistance and assured markets, concerns persist that benefits are skewed towards merchancts rather than smallholder farmers. This study investigates the determinants of smallholder participation in tobacco contract farming in ward 22, Svosve communal area, Marondera District, Mashonaland East Province. Guided by the New Institutional Economics(NIE) theory, which emphasises the role of institutions in reducing transaction cost under market imperfections, a mixed methods approach was employed. Quantitative data were from 246 communal tobacco farmers using qestionnaires, while qualitative insights were gathered from 10 key informant interviews with agricultural business advisory officers(ABAO), tobacco merchants and farmer leaders. Multistage sampling was used select 5 villages;Mere 1, Mere 2, Mere 3, Neshamba and Bonda. Data were analysed using descriptive statistics and multiple linear regression in SPSS version 25. The statistics revealed that contracted farmers had higher education levels(10 years), larger landholding(mean 2.1 hacters) and greater access to irrigation(65%) than their counterparts. The regression model was statistically significant (F = 24.73, p < 0.001) with a strong explanatory power (R² = 0.68; Adjusted R² = 0.65). Results showed that landholding size (β = 0.62) and years in contract farming (β = 0.45) were the strongest positive predictors of participation, followed by irrigation access (β = 0.38), household income (β = 0.31), and education level (β = 0.29). In contrast, multiple income sources (β = -0.27) and years in general agriculture (β = -0.27) negatively influenced participation, indicating that diversified and highly experienced farmers were less inclined to join contracts. The discussion highlighted that resource endowments and institutional support drive participation, while lack of collateral and financial literacy hinder broader inclusion. The study concludes that contract farming remains a viable pathway for smallholder integration into value chains but requires reforms to ensure equitable benefits. Policy implications emphasize collateral support, farmer training, and resource provision particularly land development and irrigation infrastructure to enhance participation and productivity among smallholder farmers.